2020
DOI: 10.1590/0103-6440202002829
|View full text |Cite
|
Sign up to set email alerts
|

Dentinal Tubule Penetration of a Calcium Silicate-Based Root Canal Sealer Using a Specific Calcium Fluorophore

Abstract: Abstract This study aimed to evaluate penetrability on dentinal tubule of a new bioceramic sealer through confocal laser scanning microscopy (CLSM). A specific fluorophore (Fluo-3) was mixed with the sealer. Forty distobuccal roots from maxillary molars were selected, and root canal preparation was carried out with Wave One Gold # 35.06 instruments. Roots were randomly assigned to 4 groups according to the filling procedures: Bioceramic/Lentulo (Sealer Plus BC); Bioceramic/EasyClean group, three activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
(38 reference statements)
1
15
0
1
Order By: Relevance
“…No reliable data exist about the penetration depth of endodontic sealers others than from studies where sealers were labelled with rhodamine B [ 7 , 8 ]. Studies using a calcium marker indicated that depth of apatite crystal precipitation in the dentinal tubules is more inferior than expected from previous studies [ 4 , 7 , 9 ]. However, this technique is also not yet validated, and no method is available to evaluate the sealer penetration by direct detection of the sealer in the dentinal tubules underneath the specimen’s surface.…”
Section: Introductionmentioning
confidence: 62%
“…No reliable data exist about the penetration depth of endodontic sealers others than from studies where sealers were labelled with rhodamine B [ 7 , 8 ]. Studies using a calcium marker indicated that depth of apatite crystal precipitation in the dentinal tubules is more inferior than expected from previous studies [ 4 , 7 , 9 ]. However, this technique is also not yet validated, and no method is available to evaluate the sealer penetration by direct detection of the sealer in the dentinal tubules underneath the specimen’s surface.…”
Section: Introductionmentioning
confidence: 62%
“…Similar to several previous studies, bioceramic sealers associated with rhodamine B were used in this study (Akcay et al, 2016; El Hachem et al, 2019; Keleş et al, 2018; Sigadam et al, 2020). Furtado et al (2020) stated that bioceramic sealers should not be used associated with rhodamine B, because the water necessary during setting of the sealer may attach to the hydrophilic rhodamine B instead of the bioceramic sealer (Coronas et al, 2020). Therefore, the use of bioceramic sealers associated with rhodamine B may have affected the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results presented statistically significant differences in some testing conditions, supporting the n in each group was sufficient. Comparison between the different root thirds (apical, middle and coronal) provided essential information regarding the different anatomical characteristics and material behavior in each area, as explored in several papers [28][29][30][31]. In this study, we focused on the apical and middle thirds, since the sealer penetration in these areas is fundamental to the success of endodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of rhodamine B, Fluo-3 is a nonfluorescent compound that binds selectively to the calcium present in calcium silicate-based sealer. The presence of these ions increases fluorescence, decreasing false-positive results when compared to other dyes, namely rhodamine B [28,34].…”
Section: Discussionmentioning
confidence: 99%